PENGEMBANGAN INFRASTRUKTUR TRANSPORTASI DI PROVINSI NUSA TENGGARA TIMUR - Sitorus, Christina Natalia; Sitorus, Budi (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2017)
Â The purpose of this research is to identify the existing condition of East Nusa Tenggara (NTT) region in the provision of road and transportation infrastructure development and the provision of connectivity. The research method used is descriptive qualitative research methodology with policy analysis approach. Data collection uses secondary data obtained from various sources and processed for analysis and evaluation. East Nusa Tenggara Province has an area of 4,734,990 hectares with a total population of 5,036,687. From the total population, there are poor people of 1.1500.080 people or equal to 22.01 %. NTT province has a wide range of potential areas such as food crops, agriculture, plantations, livestock, forestry, fisheries and marine, and mining. Those resources along with human resources are expected to improve the welfare and economic growth of people in disadvantaged areas.